Development of PjBL-based science student worksheets to improve the engineering design process and learning outcomes of elementary school students - Eko Setiyawan Dwipranoto; Rif’ati Dina Handayani; Bevo Wahono (Elementary Teacher Education Program, Majalengka University, 2025)
Students' 4C skills need to be facilitated in 21st century learning. It can be trained with various learning resources. However, the books is still the majority of learning resources in the classroom. One solution is to compile student’s worksheets as a learning resource that is integrated an innovative PjBL learning model. The student’s worksheets developed must be valid, practical, and effective in use. The student’s worksheets needs to be tested to measure the value of its validity, practicality, and effectiveness. The student’s worksheets uses the 4D model and this development process is discussed sufficiently at the develop stage. The research instruments used are student’s worksheets validation sheets, student’s worksheets implementation sheets, learning outcome tests, and student response questionnaires. The trial was conducted at SD Negeri Kedungrejo 02, Lumajang Regency with 16 students. Before it used, the student’s worksheets was validated by 2 experts and 1 certified ASN teacher who obtained an average validation score of 81.3 with a very valid category. After the student’s worksheets was declared valid, it was tested in the classroom and the practicality score obtained an average of 97.2% with a very practical category Meanwhile, the effectiveness in terms of n-gain was obtained with an average of 0.73 with details of 0.75 for learning outcomes and 0.70 for EDP, both of which are included in the high value with the effective category. The results of this trial indicate that the student’s worksheets developed meets the validity, practicality, and effectiveness values for use in classroom learning.